MiR-146a Ameliorates Hemoglobin-Induced Microglial Inflammatory Response via TLR4/IRAK1/TRAF6 Associated Pathways - Liu, Guang-Jie; Zhang, Qing-Rong; Gao, Xuan; Wang, Han; Tao, Tao; Gao, Yong-Yue; Zhou, Yan; Chen, Xiang-Xin; Li, Wei; Hang, Chun-Hua (Frontiers in Neuroscience, 2020)
Microglial activation and sustained inflammation in the brain can lead to neuronal damage. Hence, limiting microglial activation and brain inflammation is a good therapeutic strategy for inflammatory-associated central nervous disease. MiR-146a is a promising therapeutic microRNA, since it can negatively regulate the inflammatory response. We thus investigated the expression changes of miR-146a after experimental induction of a subarachnoid hemorrhage in vivo and in vitro, and we assessed the anti-inflammatory effects of miR-146a in microglial cells in vitro. Primary microglial cells were preincubated with miR-146a before hemoglobin (Hb) treatment. The results indicated that miR-146a decreased gene expression of Hb-induced pro-inflammatory cytokines (TNF-α and IL-1β) and phenotype-related genes (iNOS and CD86) through IRAK1/TRAF6/NF-κB or MAPK signaling pathways, suggesting its pro-resolution activity in microglia. However, contrary to the LPS-induced microglia or macrophage activation model, we did not observe an elevation in miR-146a after activation. Overall, our findings demonstrated that miR-146a was involved in the regulation of brain inflammation and could be considered a novel therapeutic agent for treating brain inflammation.